2022
DOI: 10.1108/lodj-05-2021-0234
|View full text |Cite
|
Sign up to set email alerts
|

New venture top management team's shared leadership and its indirect effect on strategic performance: findings from SEM and fsQCA

Abstract: PurposeThe purpose of this study is to empirically explore the relationship between a new venture top management team's (NVTMT’s) shared leadership and strategic performance in opportunity recognition and entrepreneurial bricolage by drawing on the upper echelons theory.Design/methodology/approachData were collected from 344 new manufacturing ventures located in Eastern China. The hypotheses were tested using structural equation modelling (SEM) through the AMOS 23.0 software package. The confluence of the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 88 publications
(168 reference statements)
1
8
0
Order By: Relevance
“…EOR is the advantage of satisfying a market need, interest, or desire using resource combination in a novel way to provide superior value [36]. EOR is a vital decision-making stage that is expected to increase entrepreneurs' capacity to capitalize on opportunities by promoting a flow of resources and social capital [37]. Therefore, the inclusion of EOR in the link between the EL and ES of micro-businesses is critical to developing the current model and capturing a holistic view.…”
Section: Theoretical Groundmentioning
confidence: 99%
See 3 more Smart Citations
“…EOR is the advantage of satisfying a market need, interest, or desire using resource combination in a novel way to provide superior value [36]. EOR is a vital decision-making stage that is expected to increase entrepreneurs' capacity to capitalize on opportunities by promoting a flow of resources and social capital [37]. Therefore, the inclusion of EOR in the link between the EL and ES of micro-businesses is critical to developing the current model and capturing a holistic view.…”
Section: Theoretical Groundmentioning
confidence: 99%
“…Entrepreneurship research has demonstrated the beneficial impact of leadership on the identification and exploitation of chances for new businesses. [37]. Academics have consistently recommended EL as the most effective leadership style for dealing with challenging and complex environments as well as promoting and enhancing EOR in all businesses, including MSMEs [21,[24][25][26].…”
Section: Entrepreneurial Leadership and Entrepreneurial Opportunity R...mentioning
confidence: 99%
See 2 more Smart Citations
“…Literature [13] used a combination of multiple data to investigate the methods of composing high-performance competencies, challenged the multidimensional competencies of managers under the perspective of performance, and discussed the effectiveness of the strategic management model. Literature [14] made a hypothesis on the relationship between shared leadership and strategic performance based on team theory, which was verified using structural equation modeling, and the study showed that shared leadership contributes to strategic performance in an entrepreneurial environment. Literature [15] applied strategic performance metrics to the strategic decision-making process of enterprises, investigated the impact of SPM methodology on the internal performance of enterprises, and verified the impact based on regression analysis and correlation analysis, which provided a foundation for the application of SPM in the strategic decision-making of enterprises.…”
Section: Introductionmentioning
confidence: 98%